Membrane Lipid Biosynthesis in Chlamydomonas reinhardtii. In Vitro Biosynthesis of Diacylglyceryltrimethylhomoserine - Moore, Thomas S. (American Society of Plant Physiologists, 2001)
Diacylglyceryltrimethylhomo-Ser (DGTS) is an abundant lipid in the membranes of many algae, lower plants, and fungi. It commonly has an inverse concentration relationship with phosphatidylcholine, thus seemingly capable of replacing this phospholipid in these organisms. In some places this replacement is complete; Chlamydomonas reinhardtii is such an organism, and was used for these investigations. We have assayed headgroup incorporation to form DGTS in vitro. The precursor for both the homo-Ser moiety and the methyl groups was found to be S-adenosyl-L-Met. DGTS formation was associated with microsomal fractions and is not in plastids. By analogy with phosphatidylcholine and phosphatidylethanolamine biosynthesis in higher plants, the microsomal activity probably is associated with the endoplasmic reticulum. The pH optimum for the total reaction was between 7.5 and 8.0, and the best temperature was 30°C. The apparent K(m) and V(max) for S-adenosyl-L-Met in the overall reaction were 74 and 250 μm, respectively.